Pengaruh Faktor Perilaku 3M Plus dengan Kejadian Demam Berdarah Dengue di Indonesia: A Meta Analysis - Achmad Risyaf Alfalakh (Media Gizi Kesmas, 2023)
Background: Dengue virus from DHF mosquitoes, until now there is no very good drug or vaccine to prevent and treat DHF, the activities that have been carried out so far have been to improve programs to prevent increase in mortality and vector control. Indonesia generally conducts eradication of mosquito nests which is main activity of preventing dengue cases. This activity requires community intervention. 3M Plus is an effective activity which is carried out by the community by controlling environment, biologically and chemically. Objective: To apply a meta-analysis method for several journals regarding behavioral factors of 3M plus on incidence of dengue hemorrhagic fever in Indonesia and compare the results of the summary effect using Maximum Likelihood and DerSimonian-Laird methods. Methods: Using unobtrusive research with a meta-analysis method to find the difference in estimated maximum likelihood and dersimonian-laird values "‹"‹on 3M Plus behavioral factors on incidence of dengue hemorrhagic fever in Indonesia with a case control study design. Research from March to May 2021 conducted a search for primary research sites providing journals or articles that have been published in Indonesia in last 10 years and include results of odds ratio value and compare results between two methods. Results: resulted in a heterogeneous study p value < 0.001; I² = 98.525% > 50%, CI 95, there are variations between studies regarding 3M Plus behavioral factors on incidence of Dengue Hemorrhagic Fever, right model is random effect, resulting p-values "‹"‹are both <0.05. There is a relationship between the behavioral factors of 3M Plus on the incidence of DHF in Indonesia. Conclusion: The results the meta-analysis showed a significant relationship with the summary effect of 5,84 (95% CI). The difference in parameter estimation between the Maximum likelihood and DerSimonian-Laird methods shows the same results.